2017
DOI: 10.1111/trf.14249
|View full text |Cite
|
Sign up to set email alerts
|

The effects of storage of red blood cells on the development of postoperative infections after noncardiac surgery

Abstract: BACKGROUND: Prolonged storage of red blood cells (RBCs) is a potential risk factor for postoperative infections. The objective of this study was to examine the effect of age of RBCs transfused on development of postoperative infection. STUDY DESIGN AND METHODS: In thisprospective, double-blind randomized trial, 199 patients undergoing elective noncardiac surgery and requiring RBC transfusion were assigned to receive nonleukoreduced RBCs stored for not more than 14 days ("fresh blood" group, n 5 101) or for mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…All clinical and demographic data were recorded and a written informed consent was taken from all patients enrolled. According to local transfusion policy, RBC transfusions were initiated by the attending physician, to keep patients' hemoglobin (Hb) between 7 and 9 g/dL.…”
Section: Methodsmentioning
confidence: 99%
“…All clinical and demographic data were recorded and a written informed consent was taken from all patients enrolled. According to local transfusion policy, RBC transfusions were initiated by the attending physician, to keep patients' hemoglobin (Hb) between 7 and 9 g/dL.…”
Section: Methodsmentioning
confidence: 99%
“…The decision to transfuse was made by the physician in charge of the patient according to our local transfusion policy, which includes [20][21][22] the following:…”
Section: Transfusion Policymentioning
confidence: 99%
“…Our study found that these transfusions are more common when an infection exists, which is in line with similar studies carried out by other authors (Michalia et al, 2012). Spadaro et al (2017) indicated that the storage of blood products could be an influence for the occurrence of infections. It has been noted that blood transfusions may influence a trauma patient's immune system (National Clinical Guideline Center, 2016; Sparrow, 2010).…”
Section: Discussionmentioning
confidence: 99%